Formative Modeling of Foster Care Work: A Cognitive Work Analysis Approach. (September 2021) - Wurst, Connor; Chen, Huei-Yen Winnie; Joseph, Kenneth
In this paper we present the promise of the Cognitive Work Analysis (CWA) methodology, particularly abstraction hierarchy modeling, in the foster care domain. There is increasing interest in applying machine learning decision aids to foster care decision making, but that interest is accompanied by concerns that those aids may perpetuate systemic bias or be largely context-blind. Modeling the work conducted at different levels of the domain offers unique insights into where bias may enter the system as well as possible design implications for these future decision aids. This project models two major areas of work in the domain, management of individual cases and management of overall programs offered. These work areas are then considered in the first 3 levels of the abstraction hierarchy to display the promise that this model can hold for the domain in future work, particularly when supported with more naturalistic studies.